ICT material development processes for e-learning. (2021) - Subbulakshmi, M.; Ponshanmugakumar, A.
Abstract: This paper takes the position that learning materials should in a perfect world be driven by learning and showing standards rather than grew improvised or in impersonation of top of the line course books. In short audits, the writing contributes totally towards the high-principled improvement of ELT materials and remarks on its suggestions for materials composing. At that point, six standards of language procurement that the creator thinks should tend loads a ton of consideration in materials advancement. It traces and legitimizes each rule so gets from it materials improvement standards and methods that teachers and materials journalists may apply to the specific advancement of materials.